Monitoring and Evaluation of Innovation Platforms - International Livestock Research Institute (International Livestock Research Institute, 2015)
Design and pilot processes and tools for monitoring and evaluating the impact of innovation platforms. To learn more about this dataset, please visit the ILRI Dataset Portal http://data.ilri.org/portal/dataset/innovation_platform_m_e